Research on distributed dynamic traffic data mining based on vehicular ad hoc network. (10th September 2019) - Jian, Gao
There are some problems in current traffic data mining methods, such as poor accuracy, high energy consumption, high packet loss rate and lengthy times. A distributed dynamic traffic data mining method based on vehicular ad hoc network is proposed. Before mining, congestion, routing changes, data channel errors and connection interruptions in vehicular ad hoc networks are detected respectively. Particle Swarm Optimisation (PSO) is introduced to realise traffic data classification mining based on vehicular ad hoc networks under network coding and clustering fusion. The simulations results show that the method has high accuracy and efficiency, low-energy consumption and packet loss rate, and high feasibility.